Twin Deficits in Suriname: An Empirical Analysis - Peggy Tjon Kie Sim-Balker; Albert Mungroo; Natalie Piqué-Lont; Gavin Ooft (Centrale Bank van Suriname, 2014)
This study investigates the relationship and directionality between the overall fiscal balance and the external current account balance of Suriname during 1970 - 2011. Both balances predominantly show deficits, however since 2006 the external current account balance shows surpluses due to the diversification of the mining sector as a result of booming international commodity prices. A vector error correction framework indicated the existence of a long-run relationship between these two variables. In the long run a bidirectional relation was found between the two balances, while in the short run no significant effect was encountered.
Additional information: The views expressed in this research paper are those of the authors and do not necessarily represent those of the Centrale Bank van Suriname. Research papers describe research in progress by the authors and are published to elicit comments and to further debate.
Keywords: E62; F32; F41; 330; Twin Deficits; Budget Balance; Current Account Balance